FACTORS RELATED TO DEGREE HYPERTENSION IN THE ELDERLY AT SIMPANG IV SIPIN HEALTH CENTER CITY JAMBI YEAR 2022 - Sodikhoh, Jamiatus; Nurhusna, Nurhusna; Subandi, Andi (Jurnal Keperawatan Universitas Jambi, 2024)
Background: The prevalence of hypertension sufferers continues to increase every year. Hypertension on elderly occupy order First as disease No infectious. There is Several factors are thought to cause hypertension in the elderly including genetics, obesity, age,type sex, stress, And smoke. By Because That researcher want to see factors Which related to the degree of hypertension in the elderly at Simpang IV Sipin Health Center. This research is quantitative with a Cross Sectional approach . The population in this study is all hypertensive elderly who received treatment at theSimpang IV Sipin Community Health Center with a sample size of 96 respondents using purposive sampling technique. This analysis was carried out univariately And bivariate with use test Kendall's You know And Chi-Square . Results study This It was found that factors related to the degree of hypertension in the elderly included age, gender, and stress. The research results showed a relationship between age and the degree of hypertension with ρ-value =0.002 (p<0.05), connection between type sex with degrees hypertension ρ- value =0.021 (p<0.05), connection between stress with degrees hypertension ρ-value =0.00 (p<0.05), the relationship between smoking and the degree of hypertension ρ-value = 0.542 (p <0.05). It is concluded that there is The relationship between age, gender, stress and the degree of hypertension in the elderly. So it's expected Nurses can provide information about hypertension so that they can increase knowledge client